-2(2x-5)=3x+7-x+3

Simple and best practice solution for -2(2x-5)=3x+7-x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2x-5)=3x+7-x+3 equation:


Simplifying
-2(2x + -5) = 3x + 7 + -1x + 3

Reorder the terms:
-2(-5 + 2x) = 3x + 7 + -1x + 3
(-5 * -2 + 2x * -2) = 3x + 7 + -1x + 3
(10 + -4x) = 3x + 7 + -1x + 3

Reorder the terms:
10 + -4x = 7 + 3 + 3x + -1x

Combine like terms: 7 + 3 = 10
10 + -4x = 10 + 3x + -1x

Combine like terms: 3x + -1x = 2x
10 + -4x = 10 + 2x

Add '-10' to each side of the equation.
10 + -10 + -4x = 10 + -10 + 2x

Combine like terms: 10 + -10 = 0
0 + -4x = 10 + -10 + 2x
-4x = 10 + -10 + 2x

Combine like terms: 10 + -10 = 0
-4x = 0 + 2x
-4x = 2x

Solving
-4x = 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-4x + -2x = 2x + -2x

Combine like terms: -4x + -2x = -6x
-6x = 2x + -2x

Combine like terms: 2x + -2x = 0
-6x = 0

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| x+75+x+115=180 | | 10(x+5)=9(x+5) | | 10(1-2x)=-5(2x-1) | | 9x+9=86-5x | | 8(y+7)=10y+56 | | x+2x+2x-50=3950 | | X-26=180 | | x+138+58+x=180 | | 5*x-x=240 | | 1=1/5(35x+5) | | 1=1/5(35x+15) | | 10x-102=3x-11 | | 8+1.6x=0 | | 13x+48=8x-47 | | 11x-2=10+9x | | 6.3+x=2.7 | | x+9*4=117 | | 2(g-1)=5g-17 | | -6+7x=6(2x-1) | | 7z-5=-50+2z | | x+90=80 | | 4x-(x+1)=1 | | (x+2)-x=2(x+1) | | 13x-1=13x-1 | | 4(x+3)=2(x+6) | | -6*-4+6-3+2=18 | | x^3+20=-4x^2-8x+60 | | -5(4y-3)=4(1-6)+12 | | 6y+1=3 | | 4y-9=-16+3y | | 90-7x=20x+24 | | 13x+2=12x+8 |

Equations solver categories